2014
DOI: 10.1063/1.4863950
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally driven atomistic model of 1,2 polybutadiene

Abstract: Absence of annealing effect in the vibrational density of states in a glassforming polymerWe present an efficient method of combining wide angle neutron scattering data with detailed atomistic models, allowing us to perform a quantitative and qualitative mapping of the organisation of the chain conformation in both glass and liquid phases. The structural refinement method presented in this work is based on the exploitation of the intrachain features of the diffraction pattern and its intimate linkage with atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…The main principle behind this approach is the possibility to utilize computer generated models to reconstruct the scattering and compare it with the experimentally observed structure factor in a Reverse Monte Carlo approach [17]. By accurately extracting the chain conformation from the high Q scattering region (WANS) [17]- [19] we can reconstruct the polymer structure and build a coarse-grain model to account for the crystal lamellas [20] that can be driven and evaluated by the actual experimental data in a similar manner to the simple case of the amorphous polymer (Figure 15).…”
Section: Neutron Scattering Over Several Length Scalesmentioning
confidence: 99%
“…The main principle behind this approach is the possibility to utilize computer generated models to reconstruct the scattering and compare it with the experimentally observed structure factor in a Reverse Monte Carlo approach [17]. By accurately extracting the chain conformation from the high Q scattering region (WANS) [17]- [19] we can reconstruct the polymer structure and build a coarse-grain model to account for the crystal lamellas [20] that can be driven and evaluated by the actual experimental data in a similar manner to the simple case of the amorphous polymer (Figure 15).…”
Section: Neutron Scattering Over Several Length Scalesmentioning
confidence: 99%
“…In other words, the structure factor can be considered the driving force of the model (i.e., energy), and σ corresponds to the temperature. In principle, any type of statistical test for comparison of that observed with the simulated structure factor can be used, but the χ 2 is typically used due to simplicity [6,13,31]. It can be shown that for a structural system with only pairwise forces, the RMC procedure leads to an exact solution.…”
Section: The Rmc Methodsmentioning
confidence: 99%
“…In Figure 3, the broad Q neutron scattering results for two of the individual components (protonated and deuterated 1,4 and 1,2 polybutadiene) and the resulting blends can be seen. Information regarding the sample preparation and experimental procedure for the individual components can be found elsewhere [6,31] and for the blends in the Supportive Information. Clearly, qualitative differences between the different structure factors exist (as expected) but the data quality and extent of Q range are visible.…”
Section: Local Mixing In Polymer Blendsmentioning
confidence: 99%
See 2 more Smart Citations